DUAL INCOME TAX - AN OPTION FOR THE REFORM OF PERSONAL INCOME TAX IN SERBIA? - Ranđelović, Saša (Economic Annals, 2008)
Contemporary tax theory and practice provides two fundamental concepts for taxation of personal income: scheduler and global. Several systems have been derived from these basic models, including combined, flat, dual and negative income tax. Dual income tax, the subject of this paper, requires progressive taxation of income from employment and proportional taxation of income from capital. However, strict application of this system significantly violates the principle of equitability of taxation, both horizontally and vertically.